2007
DOI: 10.1200/jco.2006.07.9194
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Low-Dose Paclitaxel and Cisplatin in Combination With Split-Course Concomitant Twice-Daily Reirradiation in Recurrent Squamous Cell Carcinoma of the Head and Neck: Results of Radiation Therapy Oncology Group Protocol 9911

Abstract: Despite a high incidence of grade 5 toxicity, 1- and 2-year OS rates for split-course bid radiation therapy and concurrent cisplatin/paclitaxel exceed results generally seen with chemotherapy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
272
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(303 citation statements)
references
References 26 publications
12
272
2
5
Order By: Relevance
“…3) A two drug combination during radiotherapy has an higher acute severe toxicity (neutropenia, anemia, oropharyngeal mucositis, weight loss) compared to cisplatin every three weeks ; 4) Tumour recurrence can be effectively treated with re-irradiation + CHT, obtaining long lasting complete remissions: this is in accordance with recent reports [20][21][22].…”
Section: Discussionsupporting
confidence: 80%
“…3) A two drug combination during radiotherapy has an higher acute severe toxicity (neutropenia, anemia, oropharyngeal mucositis, weight loss) compared to cisplatin every three weeks ; 4) Tumour recurrence can be effectively treated with re-irradiation + CHT, obtaining long lasting complete remissions: this is in accordance with recent reports [20][21][22].…”
Section: Discussionsupporting
confidence: 80%
“…Given the limited number of patients, this result should be interpreted with caution. Concurrent chemotherapy and reirradiation has been investigated in the phase II RTOG study 99‐11 28. Reirradiation with cisplatin and paclitaxel was given to 105 patients with recurrent or second primary head and neck cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the most frequently used chemotherapeutic agent for patients with esophageal cancer was paclitaxel, and commonly combined with DDP and/or 5-Fu, due to the synergic effect of the combination (Polee et al, 2002;Bucci et al, 2004 ;Orditura et al, 2010;Mirinezhad et al, 2012). Low-dose, continuous infusional paclitaxel is reported to maximally inhibit cancer through reducing the emergence of drugresistant tumor cells (Shade et al, 1998(Shade et al, -1999Langer et al, 2007;Bhatt et al, 2010). After an initial report with a response rate of 27% among taxane-resistant patients with breast cancer (Seidman et al, 1996), subsequent trials suggested that the treatment efficacy was improved (Holmes et al, 1998;Markman et al, 1998;Socinski et al, 1998;Socinski et al, 1999;Breathnach et al, 2000).…”
Section: Discussionmentioning
confidence: 99%